Mathematical modeling of the seasonal changes of phytoplankton growth in the water intake„Vidsichne” of the river teteriv - Аристархова, Ела Олександрівна; Пількевич, Ігор Анатолійович (Eastern-European Journal of Enterprise Technologies, 2013)
Despite the wide application of mathematical modeling to determine the characteristics of phytoplankton growth in basins, until now there had not been created sound mathematical models that would take into account the diversity of groups of planktonic algae for the basins of the river Teterev. Based on the research conducted in 2006-2008 the article approximates the growth of six groups of phytoplankton of water intake "Vidsichne" using the polynomial of the 6th degree and the basic criteria of the adequacy of mathematical models. The method of consolidation of intervals and replacement of the original number by medium-range intervals was applied in the research. To construct mathematical models the smoothing using moving average was carried out. As a result of processing of the data the major pathogens of "bloom" of water among groups of planktonic algae were revealed and the most dangerous periods of water pollution with their metabolites were identified. The research provided mathematical models that describe the dynamics of the growth of phytoplankton in the water intake, and multiple correlation coefficients, indicating the adequacy of these models